ADHD Comorbidity Structure and Impairment: Results of the WHO World Mental Health Surveys International College Student Project (WMH-ICS). Issue 8 (June 2022) - Mak, Arthur D. P.; Lee, Sue; Sampson, Nancy A.; Albor, Yesica; Alonso, Jordi; Auerbach, Randy P.; Baumeister, Harald; Benjet, Corina; Bruffaerts, Ronny; Cuijpers, Pim; Ebert, David D.; Gutierrez-Garcia, Raúl A.; et al.
Objective: To examine the prevalence of ADHD and the association of comorbid disorders, and multivariate disorder classes with role impairment in college students. Method: About 15, 991 freshmen (24 colleges, 9 countries, WMH-ICS) (response rate = 45.6%) completed online WMH-CIDI-SC surveys for 6-month ADHD and six 12-month DSM-IV disorders. We examined multivariate disorder classes using latent class analysis (LCA) and simulated a population attributable risk proportions (PARPs) of ADHD-related impairment. Results: About 15.9% had ADHD, of which 58.4% had comorbidities. LCA classified ADHD respondents to pure (42.9%), internalizing (36.0%), bipolar comorbidities (11.3%), and externalizing disorder classes (9.8%). ADHD, comorbidities, and multivariate disorder classes independently predicted severe impairment. PARPs: eliminating ADHD hypothetically reduced severe impairment by 19.2%, 10.1% adjusted for comorbidities, 9.5% for multivariate disorder classes. Conclusions: ADHD and comorbid disorders are common and impairing in college students. Personalized transdiagnostic interventions guided by multivariate disorder classes should be explored.